Social Work and its Discontents Under Neoliberal Conditions: The Rhetorics and Realities of the Concept „Inclusion“ - Seifert, Ruth (Ревија за социјална политика/Journal of Social Policy, 2015)
A spectre is haunting European social policies and European socialwork – the spectre of „inclusion“. During recent years, the terms„exclusion“ and „inclusion“ have become central concepts in politics, thesocial sciences and last not least social work. Social exclusion has beendeclared to be one of the core problems of social work (cf. e.g. Sheppard207, 5ff.). Despite a formidable career which the concept has made inpolitics and academia, turning up in each and every context and corner ofthe social work discourse, from the very beginning its lack of clarity andanalytical lucidity has been critizised (cf. e.g. Anhorn 2008). Thus, theterm exclusion – and the demand for inclusion - is used for completelydifferent empirical phenomena such as long-term unemployment,migrants, homosexuals, lesbians, transsexuals, ethnic groups and peoplewith impairments or disabilities – groups and individuals that presumablyare not exposed to the same mechanisms of exclusion and whose„exclusion“ takes very different forms.